Ecolinguistics and the Preservation of Linguistic Diversity in the Age of Globalization - Suparman, Suparman; Sani, Hasrul (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2025)
This study explores the role of ecolinguistics in preserving linguistic diversity amid globalization, where dominant world languages threaten the survival of local and indigenous tongues. Grounded in the ecolinguistics view that language is part of the ecological system, the research examines how linguistic diversity supports cultural and environmental sustainability. Employing a qualitative multi-method design-combining Critical Ecolinguistics Discourse Analysis (CEDA), documentary review, and comparative case studies-the study analyzes policies, media narratives, and community practices influencing language vitality. Data were collected from policy documents, UNESCO reports, NGO publications, and media texts on language endangerment and revitalization. Findings show that language loss parallels ecological degradation, as languages encode environmental knowledge and sustainable traditions vital for human–nature balance. Globalization’s ideologies of progress and uniformity foster linguistic homogenization, resembling the ecological impact of monocultures. Ecolinguistics highlights the “stories we live by” (Stibbe, 2021)—discourses that either sustain or threaten both linguistic and ecological diversity. Revitalization movements reveal that linking language with ecological awareness strengthens identity and community resilience. Ultimately, ecolinguistics offers both analytical and practical tools for integrating language preservation into sustainability agendas, aligning linguistic and ecological justice to build sustainable futures for people and the planet